Right to live and right to die: a religious and legal look at euthanasia (2018)
Over the years, the debates on the right to live and right to die (euthanasia) have evoked avalanche of human sentiments from scholars. Previous studies so far carried out have focused mainly on the medical, moral and psychological perspectives with little attention paid to the religio-legal dimension in the entire discourse. This is the gap in scholarship that this work intends to fill. That is, a consideration of the camps of irreconcilable proponents and opponents of euthanasia in the Contemporary society from the religious and legal angles. The study employs qualitative method in carrying out this research. The paper finds out, among other things, that the rate of euthanasia can be brought to the barest minimum if both religious leaders and the judiciary take the bull by the horns in addressing the various issues that make euthanasia to become rampant in the society. This paper therefore examines the meaning of euthanasia, the argument for and against and the Position of the three major religions in Nigeria and the law in the discourse. Recommendations are also offered on how to treat terminally sick person in the society.